(untitled) (ESMAT Magazine, 2018)
Rousseau’s conception of education was the subject of a very controversial reception. Beyond the debates on pedagogical postures, the originality of its approach is to propose an integrated vision of human rights by articulating the principles of freedom, equality and dignity. In this he prefigures the modern architecture of human rights. Furthermore, Rousseau’s articulation of civil and political rights, and economic, social and cultural rights, implicitly announce the notions of the indivisibility and universality of the contemporary vision of human rights.